Sustainable fashion trends and purchasing pattern analysis for textiles and apparel: An encouragement for eco-innovation - Zebran Khan; Ariba Khan; Mohd Arwab; Zeba Khanam (Sustainable Futures)
The global fashion industry is witnessing a notable shift toward sustainability, with consumers increasingly favoring environmentally friendly and socially responsible apparel. To address this trend, the present study investigates the factors influencing purchase behavior toward sustainable apparel by integrating the Theory of Planned Behavior (TPB) and examining the moderating role of environmental consciousness. Based on 288 valid responses collected through an online survey of Indian apparel consumers, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the measurement and structural models. The results reveal that electronic word of mouth (eWOM), attitude, subjective norms, and perceived behavioral control all exert a significant and positive influence on purchase behavior toward sustainable apparel. Furthermore, environmental consciousness is found to positively moderate the relationships between eWOM, attitude, and subjective norms, thereby strengthening their impact on consumer behavior. To the best of our knowledge, this study is among the first in the Indian context to explore the moderating role of environmental consciousness in the sustainable apparel domain, offering valuable insights for marketers and policymakers aiming to foster sustainable consumer practices.